Risk Behaviors Among HIV-Positive Gay and Bisexual Men at Party-Oriented Vacations - Fisher, Michael P. (Rutgers University, 2013)
OBJECTIVE: This study examined substance use (intended and actual), unprotected sex, and HIV disclosure practices (disclosure and questioning) among HIV-positive men who have sex with men (MSM) at two party-oriented vacations, where substance use and sexual risk may be heightened. METHOD: A random sample of 489 MSM attending one of two party-oriented vacations participated in PartyIntents, a short-term longitudinal survey. Nearly half (47%) completed a follow-up assessment at the event or online for up to 2 weeks after the event. We examined rates of baseline intentions to use substances, actual substance use, and unprotected intercourse among HIV-positive men in attendance.Rates among HIV-negative men were estimated for comparison. Multiple logistic regression was used to assess the impact of illegal drug use and HIV status on unprotected anal intercourse (UAI). RESULTS: HIV-positive attendees (17%) were significantly more likely than HIV-negative attendees to use nitrite inhalants (or “poppers”) (24.3% vs. 10.7%). HIV-positive attendees were also significantly more likely to have insertive UAI (64.3% vs. 34.1%) and receptive UAI (68.8% vs. 22.2%). Multivariate models showed associations between HIV status and illegal drug use with UAI (for HIV status, odds ratio [OR] = 4.5, p = .001; for any illegal drug use, OR = 16.4, p < .001). There was no evidence that the influence of drug use moderated risk by HIV status. Rates of HIV disclosure and questioning did not differ by HIV status. CONCLUSIONS: HIV-positive men attending these events engaged in higher rates of illegal drug use and sexual risk than HIV-negative men. Prevention campaigns targeting MSM at high-risk events should include messages geared toward HIV-positive men.